Pengembangan E-Modul Menggunakan Aplikasi 3D Pageflip Professional Materi Teks Biografi di Kelas X SMK Negeri 2 Alasa - Johaneslim Zalukhu; Lestari Waruwu; Mastawati Ndruru (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The observation results obtained were that students tend to get bored studying using existing printed books. The purpose of this research is (1) to develop e-modules. (2) to determine the feasibility of the e-module (3) to determine the practicality of the e-module, (4) to determine the effectiveness of the e-module. The method used is ADDIE which has 5 stages consisting of analysis, design, development, implementation, and evaluation. Based on the results of research by validation by material experts, the first revision was 56%, the second revision was 75.8% and the third revision was 94.8%. The results of validation by linguists in the first revision were 71%, the second revision was 78% and the third revision was 100%. The results of validation by media experts in the first revision were 52%, the second revision was 73% and the third revision was 96%. The results of individual trials were 86.6%, small group trials were 90%, and field trials were 97%. The completeness results obtained at the final evaluation reached 98.5% completeness. So, it can be concluded that e-modules can be said to be feasible, practical, and effective as learning references. Researchers suggest that through e-module media students will be motivated to learn